International Branch Campuses: Success Factors - Garrett, Richard (International Higher Education, 2018)
The article provides an overview of the second part of a report on international branch campuses (IBCs). The Observatory on Borderless Higher Education (OBHE) and the Cross-Border Education Research Team (C-BERT) are the authors of the report. IBCs continue to grow in number and variety around the world, and the report includes updated estimates and patterns by country, but previously there has been limited attention paid to the success factors of mature IBCs. Defined as campuses in place for a decade or more, the report draws on in-depth interviews with campus and institutional leaders.